2017
DOI: 10.3390/ijms18010116
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypyridinone Chelators: From Iron Scavenging to Radiopharmaceuticals for PET Imaging with Gallium-68

Abstract: Derivatives of 3,4-hydroxypyridinones have been extensively studied for in vivo Fe3+ sequestration. Deferiprone, a 1,2-dimethyl-3,4-hydroxypyridinone, is now routinely used for clinical treatment of iron overload disease. Hexadentate tris(3,4-hydroxypyridinone) ligands (THP) complex Fe3+ at very low iron concentrations, and their high affinities for oxophilic trivalent metal ions have led to their development for new applications as bifunctional chelators for the positron emitting radiometal, 68Ga3+, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 69 publications
0
48
0
1
Order By: Relevance
“…THP ligands were originally developed as iron-sequestering chelators, 25,26 and so as well as having high affinity for Ga 3+ , THP also has high affinity for Fe 3+ , Al 3+ and other oxiphilic transition metal ions. 12,13,[27][28][29] The highest molar activity that we have achieved for a THP conjugate to date is 80 MBq nmol À1 , 11,19 equating to <0.1% 68 Ga 3+ occupancy of THP in these solutions. This is comparatively low compared to other radiometallated conjugatesfor example, some DTPA-or DOTA-conjugates with 111 In can achieve specic activities up to 1 GBq nmol À1 , 30 and TRAP-conjugates with 68 Ga can achieve over 4.8 GBq nmol À1 , although the latter is obtained under reaction conditions that result in <70% RCY.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…THP ligands were originally developed as iron-sequestering chelators, 25,26 and so as well as having high affinity for Ga 3+ , THP also has high affinity for Fe 3+ , Al 3+ and other oxiphilic transition metal ions. 12,13,[27][28][29] The highest molar activity that we have achieved for a THP conjugate to date is 80 MBq nmol À1 , 11,19 equating to <0.1% 68 Ga 3+ occupancy of THP in these solutions. This is comparatively low compared to other radiometallated conjugatesfor example, some DTPA-or DOTA-conjugates with 111 In can achieve specic activities up to 1 GBq nmol À1 , 30 and TRAP-conjugates with 68 Ga can achieve over 4.8 GBq nmol À1 , although the latter is obtained under reaction conditions that result in <70% RCY.…”
Section: Introductionmentioning
confidence: 89%
“…1) that rapidly and quantitatively incorporates 68 Ga 3+ at room temperature, neutral pH, and low chelator concentrations, giving a single species. [11][12][13] It is consequently well-suited to kit-based 68 Garadiopharmceutical synthesis, unlike other common gallium chelators such as DOTA and HBED-CC. THP has demonstrated superior radiolabelling properties compared to many other chelators, with higher RCYs achievable for THP at very low concentration compared to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 68 Ga 3+ and THP Me (or THP H ) represent a potential chemical pretargeting pair. Notably, several BFC have been developed based on THP Me , including isothiocyanate (THP Me -NCS, Figure 1A) and maleimide derivatives that can effectively bind to lysine or cysteine side chains, respectively, in mild conditions (aqueous solution, mildly basic pH, room temperature), allowing facile conjugation to antibodies [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…11 DFP was extensively studied during past years by Hider [12][13][14] and Santos, [15][16][17] who prepared its oligodentate derivatives mostly as Fe(III) chelators, which ultimately found new application as Ga 68 complexes for PET immagining. 14,18,19 Recently, Abbate et al reported novel targeting peptides incorporating DFP as the iron(III) chelating units. 20 Nevertheless, there is an urgent need for other, more efficient, less toxic and cheaper aluminum chelators.…”
Section: Introductionmentioning
confidence: 99%